2007
DOI: 10.1016/j.pupt.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast exerts no acute direct effect on NO synthases

Abstract: The cysteinyl leukotrienes (CysLTs) LTC 4 , LTD 4 and LTE 4 are potent proinflammatory lipid mediators that play a central role in inflammation, contraction and remodelling of airways observed in asthmatics. Montelukast, a competitive inhibitor of the cysteinyl leukotriene-1 (CysLT 1 ) receptor attenuates asthmatic airway inflammation, contraction and remodelling. As a number of studies have shown that montelukast reduced exhaled nitric oxide (NO) levels, a marker of inflammation that correlates with the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, to the best of our knowledge, there are no scientific evidence that the LTD4-CysLT1 pathway has any role on the erectile function nor does on the NO signaling pathway. 57 A study carried out in human or guinea pig trachea showed that MK571 (19 μM) did not affect histamine-, ACh-, serotonin-, prostaglandin F2alpha-, U46619-(a stable analog of thromboxane A2), or prostaglandin D2-induced contractions. In human trachea, MK571 antagonized only LTD4-induced contraction.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, there are no scientific evidence that the LTD4-CysLT1 pathway has any role on the erectile function nor does on the NO signaling pathway. 57 A study carried out in human or guinea pig trachea showed that MK571 (19 μM) did not affect histamine-, ACh-, serotonin-, prostaglandin F2alpha-, U46619-(a stable analog of thromboxane A2), or prostaglandin D2-induced contractions. In human trachea, MK571 antagonized only LTD4-induced contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting aspect of this study is that the protection was recovered in the chronic HDM asthma model after NO supplementation by nitrite administration. The dose of nitrite used in this study was shown to deliver low-to-moderate levels of NO and protects against several oxidative stress-related conditions including hypoxic vasodilation, ischemia of the heart and liver, and postoperative ileus [ 26 , 32 , 33 ]. It is important to acknowledge that the failure of iNOS inhibition to protect against AHR in chronic asthma may be related to other factors besides NO; however, the level of the gas may constitute a major determinant in the protection against AHR.…”
Section: Discussionmentioning
confidence: 99%